please add: 4x^4-2x^2+1 and 3x^2-3x-4

4x^4-2x^2+1 + 3x^2-3x-4
4x^4 + (-2 + 3)x^2 + (-3)x + 1 - 4
4x^4 + x^2 - 3x - 3.

Expert answered|clouise|Points 359|

Question|Rated good

Asked 8/9/2012 10:05:52 PM

0 Answers/Comments

Rating

There are no new answers.

Simplify: 2+5(3b+9)-b **Weegy:** 2+15b+45-b= 47+14b (More)

Question

Expert Answered

Updated 284 days ago|6/20/2014 1:47:43 PM

0 Answers/Comments

is this true or false: 15+3x+3=3(5+x+1) **Weegy:** false
(More)

Question

Expert Answered

Updated 284 days ago|6/20/2014 1:48:59 PM

1 Answer/Comment

15 + 3x + 3 = 3(5 + x + 1);

3x + 18 = 3x + 18

The equation is TRUE.

3x + 18 = 3x + 18

The equation is TRUE.

Added 284 days ago|6/20/2014 1:48:59 PM

This answer has been confirmed as correct, not copied, and helpful.

what property is this: 2(4x+1)=2x4x+2x1 **Weegy:** 2(4x+1)=2x4x+2x1 is Distributive Property of Multiplication. **User:** thank you sooo much!! **Weegy:** You're welcome! Thanks for using Weegy! Have a nice day! (More)

Question

Expert Answered

Asked 8/5/2012 1:07:55 AM

0 Answers/Comments

is this true or false: 15+3x+3=3(5+x+1) **Weegy:** **User:** Simplify: 1+4(3b+9)-b **Weegy:** 11b+37=0
b=-37/11=-3.3636 **User:** thank you **Weegy:** You're welcome! Thank you for using Weegy! (More)

Question

Expert Answered

Updated 233 days ago|8/11/2014 12:34:42 AM

3 Answers/Comments

It is true that 15+3x+3=3(5+x+1).

3(5+x+1)

=3*5+3*x+3*1

=15+3x+3.

3(5+x+1)

=3*5+3*x+3*1

=15+3x+3.

Added 233 days ago|8/11/2014 12:29:24 AM

This answer has been confirmed as correct, not copied, and helpful.

Rated bad by jeifunk, Rated good by jeifunk, Confirmed by jeifunk [8/11/2014 12:34:39 AM], Rated good by jeifunk

Simplify 1+4(3b+9)-b is as follows:

1+4(3b+9)-b

=1+4*3b+4*9-b

=1+12b+36-b

=12b-b+1+36

=11b+37.

1+4(3b+9)-b

=1+4*3b+4*9-b

=1+12b+36-b

=12b-b+1+36

=11b+37.

Added 233 days ago|8/11/2014 12:32:44 AM

This answer has been confirmed as correct, not copied, and helpful.

solve: x-3/3+x-3/4=7/24
**Weegy:** x - 3/3 + x - 3/4 = 7/24
Simplify.
x - 1 + x - 3/4 = 7/24
Move all terms with the variable x to the left and all other terms to the right, remembering to switch signs when we switch sides.
x + x = 7/24 + 1 + 3/4
Simplify the left side. [ Find a common denominator on the right.
2x = 7/24 + 24/24 + 18/24
Add across the top on the right, now that we have a common denominator.
2x = 49/24
Divide both sides by 2.
x = 49/48
This is not in your list of answers.
Did you forget the brackets? Is this the original question?
(x-3)/3 + (x-3)/4 = 7/24
Let's try that instead.
First, we want to get rid of the fractions. Multiply each term by 24.
8(x-3) + 6(x-3) = 7
Expand and simplify.
8x - 24 + 6x - 18 = 7
Move all terms with the x to the left (already there) and all other terms to the right.
8x + 6x = 7 + 24 + 18
Simplify each side.
14x = 49
Divide by 14 and reduce.
x = 49/14 = 7/2 = 3.5
7/2 is in your list of answers. ] (More)

Question

Expert Answered

Asked 8/5/2012 1:32:32 AM

0 Answers/Comments

20,203,745 questions answered

Points 0 [Total 0]| Ratings 0| Comments 0| Invitations 0|Offline

Points 0 [Total 0]| Ratings 0| Comments 0| Invitations 0|Offline

There are no comments.